Analytical solution for transient temperature of multi-barrier system with thermal resistance in nuclear waste repository by Green's function method - Xu, Xun; Zhou, Xiangyun; Sun, De'an (International communications in heat and mass transfer, 2024)
The multi-barrier system of a nuclear waste repository consists of engineered barriers and natural barriers. The uneven surface caused by mechanical excavation at the rock wall leads to incomplete contact between bentonite and surrounding rock. The incomplete contact contributes to the decay heat conduction at the rock wall being subject to resistance, which is known as the thermal resistance effect. The mathematical model for heat conduction, in which the thermal resistance is considered, is established according to the design concept of the Swedish repository. With the Green's function method, the explicit analytical solutions to the model, which can straightforwardly represent the temperature at any spatial point and time, are derived. The rationality is verified by comparing the results of present solutions with existing solutions and numerical simulations. Based on the present solutions, the influence mechanism of thermal resistance on thermal responses within the multi-barrier system are systematically investigated. The findings indicate that the effect of thermal resistance in the bentonite is more significant than that in the rock. This effect increases during the initial stage of disposal and then decreases with the passage of time. The impact of thermal resistance on the temperature field is minimally influenced by variations in the thermal conductivities of the bentonite and rock. Furthermore, the impact of thermal resistance on the temperature distribution attenuates as the buffer layer thickness increases.